2014
DOI: 10.1530/erc-13-0551
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of androgen action in endometrial and ovarian cancers

Abstract: Endometrial cancer (EC) and ovarian cancer are common gynaecological malignancies. The impact of androgen action in these cancers is poorly understood; however, there is emerging evidence to suggest that targeting androgen signalling may be of therapeutic benefit. Epidemiological evidence suggests that there is an increased risk of EC associated with exposure to elevated levels of androgens, and genetic variants in genes related to both androgen biosynthesis and action are associated with an increased risk of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 143 publications
3
46
0
6
Order By: Relevance
“…testosterone, DHT) may play a role in ovarian carcinogenesis. 31 However, AR expression in serous carcinomas was associated with improved survival in one study (n 5 90). 35 Androgens may have a direct impact on ovarian carcinogenesis, or act via their function as precursors to estrogens.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…testosterone, DHT) may play a role in ovarian carcinogenesis. 31 However, AR expression in serous carcinomas was associated with improved survival in one study (n 5 90). 35 Androgens may have a direct impact on ovarian carcinogenesis, or act via their function as precursors to estrogens.…”
Section: Discussionmentioning
confidence: 94%
“…Androgen receptors (AR) and estrogen receptors (ER) are expressed throughout the reproductive system including ovaries, the fallopian tubes and endometrium. 31,32 Androstenedione and DHEAS have low binding affinity for AR while testosterone and dihydrotestosterone (DHT) have highest AR affinity and androgenic activity. Prior research suggests EOC tumors express the AR with differences by histological subtype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As androgens may also have roles in uterine pathology (Gibson et al 2014) and AR is expressed in many uterine cancers notably of epithelial cells (Ito et al 2002), we investigated the role of AR-mediated androgen action confined to uterine glandular epithelium in experimental, PTEN deletion-induced uterine pathology. Our study has demonstrated that glandular epithelial AR inactivation significantly enhanced and accelerated the progression of PTEN deletion-induced uterine pathology.…”
Section: Discussionmentioning
confidence: 99%
“…In the nonmalignant endometrium, AR was reported to be expressed in the endometrium throughout the menstrual cycle (Mertens et al 2001, Apparao et al 2002, Ito et al 2002, Marshall et al 2011, Gibson et al 2014. The status of AR immunoreactivity in stromal cells is higher than that of epithelial AR throughout the menstrual cycle (Apparao et al 2002).…”
Section: Androgen Receptor Expressionmentioning
confidence: 99%